Analisis Beban Kerja Fisik dan Penentuan Jumlah Tenaga Kerja pada Produksi Roller Conveyor - Mahfudzy, Shoulton Arieffudin; Widiasih, Wiwin (Fakultas Teknik UMRI, 2026)
This study aims to analyze the physical workload, fatigue levels, and determine the optimal number of workers in roller conveyor production within the machining division of PT. XYZ. Manual work processes involving continuous standing postures cause high levels of worker fatigue. This condition impacts production fluctuations, which frequently fail to achieve the monthly target of 3,217 pcs. This research utilizes Cardiovascular Load (CVL) to measure physical workload via heart rate, the 30-item IFRC questionnaire to assess subjective fatigue, and Workload Analysis (WLA) to evaluate the workload. The results showed an average %CVL of 50.02% (classified as heavy workload). Fatigue levels increased drastically from an average score of 52 (pre-work) to 68 (post-work). WLA results confirmed a workload imbalance across workstations. To achieve the 3,217-unit target, 24 workers are ideally needed, while only 20 are currently available. The company is advised to add 4 new workers and implement cross-training to balance the production line.